Mongolia : Energy Efficiency in the Electricity and District Heating Sectors - World Bank (Washington, DC, 2014)
The purpose of this Activity Completion Report is to sumarize the results of support from ESMAP to Mongolia in the rehabilitation of its electricity and district heating systems during the period 1994 to 1998. ESMAP ascertained the level and sources of losses in the electricity and district heating distribution systems in Ulaanbaatar; and propose a set of actions and investments to lower these losses to economic levels. ESMAP's research resulted in three main conclusions: 1) in the power distribution system in Ulaanbaatar, overall energy losses on the transmission and distribution (TD) system are following an upward trend, increasing from about 27 percent of the net energy supplied in 1995 to 30 percent in 2000. of these losses, about 14 percent are estimated to be technical losses and 16 percent are estimated to be non-technical losses. The major problems are occurring in the low-voltage system, as opposed to the mid-voltage system. the current cstomer relations setup and sales function must be changed for the company forto act on a commercial basis and for future privatization. 2) Water loss constitutes the major problem in the district heating system, with leakage rates well beyond internationally accepted standards. The heat loss resulting from transmission and radiation is not as serious as the water leakage. 3) This report indicates that integrating the analyses of the heat and electricity sectors would achieve higher returns.